The mercato delle erbe: via Ugo Bassi entrance, left corridor and its restaurant areas - Tamburello, Simona; Vaselli, Valeria; Vitello, Silvia (E|C, 2020)
This paper deals different aspects of the Mercato delle Erbe in Bologna. We chose to divide it into three parts: one is dedicated to the Mercato delle Erbe as a place of consumption, another part to the sound dimension, and a last part to the configuration of the limits and thresholds derived from senses such as smell and sight. It emerges that this space particularly emphasizes the poly-sensorial and synesthetic aspects of the experience. Sight and hearing help the consumer to cross the market while smell creates limits and thresholds. Other senses, however, have an important role in this space and therefore in this experience: taste is mainly present in dining areas, while touch is present in both dining areas and stalls and suggests the quality of the goods being sold. The sound experience involves the user both in a hi-fi sonic environment and in a lo-fi one, where you can distinguish sounds that create a general effect of silence or noise, respectively. Finally, we took into consideration both daytime and nighttime hours and it turned out that there is an alternation between these two types of environments throughout the day and the week.